Qualitative analysis on the diffusive Holling–Tanner predator–prey model - Zhao, Xu; Zhou, Wenshu (Electronic journal of qualitative theory of differential equations, 2023)
We consider the diffusive Holling–Tanner predator–prey model subject to the homogeneous Neumann boundary condition. We first apply Lyapunov function method to prove some global stability results of the unique positive constant steady-state. And then, we derive a non-existence result of positive non-constant steady-states by a novel approach that can also be applied to the classical Sel'kov model to obtain the non-existence of positive non-constant steady-states if 0 < p ≤ 1 .